THE IMPACT OF PROCESS, PEOPLE AND PHYSICAL EVIDENCE ON SMALL RETAIL BUSINESS PERFORMANCE IN DURBAN CENTRAL, SOUTH AFRICA - Mahohoma, N.; Agbenyegah, A.T. (The actual problems of regional economy development, 2024)
The vibrant commercial landscape of Durban Central, South Africa, is greatly influenced by the dynamic contributions of small retail businesses. Beyond their economic impact, small businesses also generate employment opportunities. However, despite their significance, small businesses are often hindered by obstacles to achieving and maintaining sustainable performance. To overcome these obstacles, it is essential to comprehend the influence of different factors on their performance. This study aims to evaluate the impact of process efficiency, people (human factor) and physical evidence (3 selected Ps) on the performance of small retail businesses. Existing research highlights the significance of these 3 selected Ps in propelling the success of small businesses, with a focus on streamlining operations, motivated staff and creating aesthetically pleasing storefronts. A quantitative approach was implemented in this study. This involved the distribution of self-completed surveys of a 5-point Likert scale questionnaire ranging from “strongly agree to strongly disagree”. 190 out of 217 small retail business owners in Durban Central completed the survey, resulting in a response rate of 87.56%. Quantitative data was analysed using the SPSS version 29. Pearson’s Chi square was used to test the formulated hypotheses. The findings showed that small retail business owner/managers hold a strong belief that there is a positive influence between the 3 selected Ps and business performance. This underlines the significance of investing in a favourable physical environment, streamlining internal processes and prioritising employee development and involvement to improve business performance. However, it is worth noting that while many businesses reported positive outcomes, there were also varying perceptions of performance among small retail businesses, indicating that external factors may also play a role in their success. It is recommended that small businesses invest in creating a friendly physical space, streamlining internal processes and providing thorough employee training and engagement.